2013
DOI: 10.4314/jasem.v17i2.16
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal evaluation of groundwater quality around Igando dumpsites in Lagos metropolis using correlation and regression analysis.

Abstract: Correlation and Multiple linear regression analysis was used to establish the degree of relationship and variability of groundwater quality parameters around Solous 1 and 2 Dumpsites, in Igando, Lagos, for the wet and the dry seasons. The correlation between TDS and other hydrochemical parameters which constituted the independent variables were positive, with significantly high positive correlation exhibited between TDS and EC for the wet season. For the dry season, the correlation between TDS and other ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Also, Olatunji et al (2015) reported the suitability of groundwater quality for drinking based on their study in Ilorin metropolis, Nigeria. Balogun and Adegun (2013) reported the high concentration of EC, TDS, Cl, and trace metals in their study around Igando. A similar study by Yidana and Yidana (2010) asserts that the WQI of the Voltaian sedimentary basin in Ghana is suitable for drinking purpose.…”
Section: Drinking Water Qualitymentioning
confidence: 93%
See 1 more Smart Citation
“…Also, Olatunji et al (2015) reported the suitability of groundwater quality for drinking based on their study in Ilorin metropolis, Nigeria. Balogun and Adegun (2013) reported the high concentration of EC, TDS, Cl, and trace metals in their study around Igando. A similar study by Yidana and Yidana (2010) asserts that the WQI of the Voltaian sedimentary basin in Ghana is suitable for drinking purpose.…”
Section: Drinking Water Qualitymentioning
confidence: 93%
“…Groundwater quality can be influenced by the lithology, water-rock interaction, and changes in space and time (Todd and Larry 2005;Srinivasamoorthy et al 2008;Bhattacharya and Bundschuh 2015).The continuous rise in anthropogenic activities, uncoordinated development, has led to an increase in point source pollutants such as leachates from dumpsite, seepage from the septic tank, and municipal sewage plants among others. Current emerging pollutants from agro-based activities such as nitrate, pesticides, and other heavy metals and persistent organic products (POPs), volatile organic carbon (VOCs) among others pose serious challenges to human health and the sustainability of groundwater (Kumazawa 2002;Jalali and Kolahchi 2008;Balogun and Adegun 2013;Salami and Susu 2013;Ocheri et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater is an essential resource that requires sufficient protection from human-induced pollution sources. Human actions and resultant climate change have affected the standard quality of both surface and underground water [1], [2], especially from newly uptake pollutants through agricultural processes, nitrate, pesticides, other heavy metals and organic products, and volatile organic carbons; are a potential danger to human health and groundwater sustainability [3], [4], [5], [6], [7]. Among other water sources, groundwater is a source of fresh water and a dependable means of water provision in Nigerian communities and was considered less contaminated by pollution to surface running waters [8]; earth's surface groundwater quality relies on other factors:-the quality of inflow water, precipitation, rural-urban dumpsites and landfill systems and significantly, the form of sewerage systems adopted in the population [9] of Nigeria's municipal wastewater treatment systems are not adopted estates and landlords have their installed domestic wastewater platforms.…”
Section: Introductionmentioning
confidence: 99%